The Effect of Cognitive Behavioral Therapy on Anxiety in Adolescents - Khan, Zuha; Zaib, Qandeel; Saeed, Kanwal; Khan, Bakhtawar; Pal, Haadi Ashal; Zaman , Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Anxiety disorders are prevalent among adolescents, significantly impacting their emotional well-being, academic performance, and social interactions. Objective: This study aimed to evaluate the effectiveness of Cognitive Behavioral Therapy (CBT) in reducing anxiety symptoms in adolescents. Methodology: The study was conducted at Holy Family Hospital, Rawalpindi, from May 1 to October 30, 2024 and included 115 participants. All participants were screened to confirm an anxiety diagnosis and completed baseline assessments using standardized tools, including the State-Trait Anxiety Inventory for Children (STAIC) and the Beck Anxiety Inventory (BAI). Results: Participants were divided into experimental and control groups with similar demographic characteristics, including mean ages of 15.4 ± 1.2 and 15.3 ± 1.1 years, respectively, and a male majority in both groups. Most participants were diagnosed with generalized anxiety disorder (GAD) (66.7% in the experimental group, 68% in the control group), while the remainder had social anxiety disorder (SAD). Baseline anxiety scores were comparable between groups, with mean BAI scores of 24.5 ± 5.2 and 23.8 ± 4.8, and STAIC scores of 38.7 ± 6.3 and 37.4 ± 5.9, respectively. Conclusion: CBT led to significant improvements in anxiety scores in the experimental group, with benefits sustained at 3- and 6-month follow-ups. These findings confirm the efficacy of CBT as a treatment for reducing anxiety symptoms in adolescents, offering a structured and evidence-based approach to managing this prevalent mental health challenge.